2021
DOI: 10.1159/000512245
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Variation in Benefit of Treatment of Congenital Unilateral Aural Atresia: A Review of the Literature

Abstract: <b><i>Objective:</i></b> A review of published data regarding binaural hearing after treatment of congenital unilateral conductive hearing loss (UCHL) due to aural atresia. Treatment options concern atresia surgery (reconstructive surgery), application of a bone conduction device (BCD), or application of a middle ear implant (MEI). <b><i>Data Sources:</i></b> Database PubMed was searched for articles published in English and German between January 1, 1994, and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Scores obtained in our work lead us to make some considerations: Our results reveal that patients of group 1 (affected by bilateral conductive or mixed hearing impairment fitted with bilateral BCI) started from lower hearing thresholds at baseline condition before treatment if compared to group 2 (affected by monaural conductive or mixed hearing loss fitted with unilateral BCI), resulting in a difference between group 1 and group 2 of 5.84 dB for the summation setting, 2.46 dB for the squelch setting and 4.84 dB for the head shadow setting at time 0. In fact, the implantation of a single BCI in subjects affected by bilateral conductive hearing loss results necessary in a disadvantaged starting condition if compared to subjects affected by unilateral hearing loss who received normal hearing input from the contralateral normal-hearing ear since their birth [ 18 ]. In our work, both groups showed a substantial decrement in the signal-to-noise ratio (SNR) at the speech recognition threshold (SRT) for all tested settings.…”
Section: Discussionmentioning
confidence: 99%
“…Scores obtained in our work lead us to make some considerations: Our results reveal that patients of group 1 (affected by bilateral conductive or mixed hearing impairment fitted with bilateral BCI) started from lower hearing thresholds at baseline condition before treatment if compared to group 2 (affected by monaural conductive or mixed hearing loss fitted with unilateral BCI), resulting in a difference between group 1 and group 2 of 5.84 dB for the summation setting, 2.46 dB for the squelch setting and 4.84 dB for the head shadow setting at time 0. In fact, the implantation of a single BCI in subjects affected by bilateral conductive hearing loss results necessary in a disadvantaged starting condition if compared to subjects affected by unilateral hearing loss who received normal hearing input from the contralateral normal-hearing ear since their birth [ 18 ]. In our work, both groups showed a substantial decrement in the signal-to-noise ratio (SNR) at the speech recognition threshold (SRT) for all tested settings.…”
Section: Discussionmentioning
confidence: 99%
“…Results on speech recognition were more diverse, where four individuals showed a worse performance in the aided setting. In a review by Vogt et al ( 33 ), they found that aided hearing thresholds did not approach normal levels in six out of nine included studies and also suggested that an insufficient degree of amplification might be a part explanation for poorer aided speech recognition scores. Several of the study participants in the present study did not reach normal hearing levels of the atretic ear in the aided setting.…”
Section: Discussionmentioning
confidence: 99%
“…For horizontal SLA in normal binaural hearing, ITDs have been shown to be dominant, overthrowing ILD and spectral cues for low frequency sounds ( 39 ). Monaural spectral cues, resulting from acoustic reflections in the pinna, shoulders, and body are used for localization in the vertical plane in normal hearing listeners ( 40 ) and might be of importance for unaided horizontal sound localization in individuals with UAA ( 8 , 11 , 33 , 34 ). Here, monaural cues were likely available to the children, but not very prominent given the naturally occurring amplitude modulations of the sound.…”
Section: Discussionmentioning
confidence: 99%
“…Brotto et al reinforce the idea that using BCIs in UCHL might improve speech perception in noise thanks to the summation effect, but the setting of the study prevented the investigation of real binaural hearing 15 . Vogt et al, in a 2021 review, suggest instead that the benefits of BCIs might be related to bilateral hearing (2 “separate” inputs) rather than “binaural hearing” (a fused concept) 16 .…”
Section: Introductionmentioning
confidence: 99%